Truth, masculinity and the anti-elitist backlash against the university in the age of Trump. Issue 5 (4th July 2018) - Read, Barbara
ABSTRACT: The global rise of 'neo-populism', culminating in the election of the populist Republican candidate Donald Trump to the US presidency, has been accompanied by a notable backlash and resistance to what has been categorised as governing/dominating 'elites', including HE academic institutions. Populist critiques centre on a perceived climate of censorship on campus in the name of 'political correctness'. In this paper I examine some of the arguments put forward by proponents and detractors in these debates, utlising some examples from empirical data from a study of online student newspaper posts in 2016 and 2017 from campuses in the US and the UK. In doing so I will be exploring the ways in which the debates are underpinned by distinct gendered, classed and 'raced' discourses that are linked not only to differing conceptions of 'truth' but also the nature and purpose of learning in the university itself.